1986
DOI: 10.1346/ccmn.1986.0340109
|View full text |Cite
|
Sign up to set email alerts
|

Lysis of Erythrocytes by Silicate Minerals

Abstract: Abstract--In vitro studies of the destruction (lysis) of bovine red blood cells (erythrocytes) by some silicate minerals showed the reaction to be complete in less than 1 hr and very destructive to the cell membrane. The activity as lysing agents was found to be in the order smectites > silica > palygorskite -~ sepiolite > chrysotile > kaolinite. Different compositions (Fe, A1, Mg, Li, vacancy) of the octahedral sheet of the smectite and fibrous clay minerals did not appreciably alter their hemolytic activity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…However, as the calcite standard was non-reactive in both the haemolysis and alamarBlue® assays, it is unlikely that calcite content is solely responsible for the different reactivity of Spanish unprocessed and flux-calcined DE. The presence of clays may also have an effect, as some clays have been shown to be more haemolytic than crystalline silica [ 59 , 60 ]. However, the lack of clay in processed DE samples and the low reactivity of French, unprocessed samples, suggests that clay minerals are not the cause of DE induced toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…However, as the calcite standard was non-reactive in both the haemolysis and alamarBlue® assays, it is unlikely that calcite content is solely responsible for the different reactivity of Spanish unprocessed and flux-calcined DE. The presence of clays may also have an effect, as some clays have been shown to be more haemolytic than crystalline silica [ 59 , 60 ]. However, the lack of clay in processed DE samples and the low reactivity of French, unprocessed samples, suggests that clay minerals are not the cause of DE induced toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Data on this subject are not conclusive. Oscarson et al (1986) studied the effect of sepiolite and palygorskite on erythrocyte lysis. They found the two minerals to be lysing agents, and structural folding to reduce lysis, thereby suggesting that edge surfaces and silanol groups are important in the process, whereas elongate morphology appears to be irrelevant.…”
Section: Palygorskite and Sepiolite Clays And Health Hazardsmentioning
confidence: 99%
“…This is significant, as smectite was found to be one of the main contributors to podoconiosis prevalence in our recent geospatial study of soil characteristics in the same geographical area in Ethiopia ([ 9 ]). Smectites are known to be highly haemolytic in assays using sheep, bovine and human RBCs (e.g., [ 46 ],[ 47 ],[ 48 ],[ 49 ]). Other studies have shown the elevated HA of clays: kaolinite and bentonite (a montmorillonite-rich deposit, commonly formed from the weathering of volcanic ash) were found to be as haemolytic as crystalline silica (Min-U-Sil), whereas feldspar (a mineral commonly found in soil samples) was less haemolytic (e.g., [ 50 ]).…”
Section: Discussionmentioning
confidence: 99%